2011
DOI: 10.1051/0004-6361/201117581
|View full text |Cite
|
Sign up to set email alerts
|

Faint high-redshift AGN in theChandradeep field south: the evolution of the AGN luminosity function and black hole demography

Abstract: Context. We present detection and analysis of faint X-ray sources in the Chandra deep field south (CDFS) using the 4 Ms Chandra observation. Aims. We place constraints on active galactic nuclei (AGN) luminosity functions at z = 3-7, its cosmological evolution, and highredshift black hole and AGN demography. Methods. We use a new detection algorithm, using the entire three-dimensional data-cube (position and energy), and searching for X-ray counts at the position of high-z galaxies in the GOODS-South survey.Res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
173
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(192 citation statements)
references
References 144 publications
19
173
0
Order By: Relevance
“…Indications along such line have been reported by several groups (Glikman et al 2011;Civano et al 2011;Fiore et al 2012), although it is fair to say that results seem not univocal (see, e.g., Masters et al 2012). Very recently, Giallongo et al (2015) found 22 AGN candidates at z 4 in the Candel/GOOD-S/Chandra Deep Field South field, which is suggestive of a prominent contribution of AGNs to the ionising background in the range 4 z 6.5.…”
Section: Introductionmentioning
confidence: 67%
“…Indications along such line have been reported by several groups (Glikman et al 2011;Civano et al 2011;Fiore et al 2012), although it is fair to say that results seem not univocal (see, e.g., Masters et al 2012). Very recently, Giallongo et al (2015) found 22 AGN candidates at z 4 in the Candel/GOOD-S/Chandra Deep Field South field, which is suggestive of a prominent contribution of AGNs to the ionising background in the range 4 z 6.5.…”
Section: Introductionmentioning
confidence: 67%
“…Cowie et al 2009;Willott et al 2010;Fontanot et al 2012), although quasars, mini-quasars and a faint AGN population could also play a significant role (e.g. Volonteri & Gnedin 2009;Fiore et al 2012;Haardt & Salvaterra 2015;Hao et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For the IT scenario, the black solid line represents the host stellar mass function predicted by the model; for the DI scenario, the red solid line represents the predictions for the fiducial case (α = 10), while the red dashed line represents the case with the normalization of the accretion rate decreased (α = 2). The blue dotted line represents the host stellar mass function estimate from Fiore et al (2012) as computed by the authors at redshift 0.75, 1.25, 2, and 3.5. The shaded region represents the observational data from Bongiorno et al (in prep.…”
Section: Stellar Mass Function Of Agn Host Galaxiesmentioning
confidence: 99%
“…We also compared our results with the empirical estimates of the host stellar mass function from Fiore et al (2012). The authors first converted the X-ray AGN luminosity functions (taken from La Franca et al 2005 for z < ∼ 2 and from their work for z > 3) into BH mass functions using Monte Carlo realizations and assuming a given Eddington ratio distribution.…”
Section: Stellar Mass Function Of Agn Host Galaxiesmentioning
confidence: 99%
See 1 more Smart Citation